1996
DOI: 10.1111/j.1476-5381.1996.tb15426.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of guinea‐pig trachea by sodium nitroprusside: cyclic GMP and nitric oxide not involved

Abstract: 1 Sodium nitroprusside (SNP) completely relaxed the guinea-pig isolated, perfused trachea in a concentration-dependent manner. Although SNP was less potent by about 2 orders of magnitude, its maximal effect was 25% higher compared to isoprenaline.2 SNP (3.2 guM) increased cyclic GMP levels by 300% and relaxed guinea-pig isolated, perfused trachea by 54%. The SNP-induced relaxations of the preparations were not affected by the guanylate cyclase inhibitor, methylene blue. Moreover, zaprinast, a cyclic GMP-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…We also found that IBMX had no signi®cant eect on the relaxation of the rabbit aorta to NO. A similar dissociation in cyclic GMP levels and relaxation in the presence and absence of zaprinast has been noted in respiratory smooth muscle (Sadeghi-hashjin et al, 1996).…”
Section: Role Of Phosphodiesterase In the Response To Nosupporting
confidence: 73%
“…We also found that IBMX had no signi®cant eect on the relaxation of the rabbit aorta to NO. A similar dissociation in cyclic GMP levels and relaxation in the presence and absence of zaprinast has been noted in respiratory smooth muscle (Sadeghi-hashjin et al, 1996).…”
Section: Role Of Phosphodiesterase In the Response To Nosupporting
confidence: 73%
“…This metabolic activation might indeed be mediated by distinct NO-generating enzymes for each of the chemical classes of compounds, which even may be organ-specific (Kowaluk et al 1992;Gordge et al 1998). There are also data indicating that elevations in tissue cGMP levels do not always explain relaxation induced by NO donors (Kuenzli et al 1996;Sadeghi-Hashjin et al 1996), and the involvement of direct effects, such as S-nitrosylation reactions with protein thiols (Arnelle and Stamler 1995;Perkins et al 1998) or even NO-independent effects (Sadeghi-Hashjin et al 1996), has been suggested. In light of these discrepancies, it is becoming obvious that data obtained using a certain agent should not be extrapolated to other compounds and it is essential to examine the mechanism of action of each chemically distinct nitrocompound in each tissue, comparing it with that of NO itself.…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that tissues in both phenotypes have enough guanylate cyclase present to fully relax them and therefore it is the lack of enough NO being released which is the deficiency in the response to carbachol in the db/db mouse. However, the use of SNP as an NO donor is controversial [26].…”
Section: Effects Of Carbachol and Snp On Phenylephrine-induced Contramentioning
confidence: 99%